Textural Properties Characterization for NaX and FeX Zeolites by Nitrogen Adsorption-desorption Technique - Kamal, Sanarya K.; Abbas, Ammar S. (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
The zeolite's textural properties have a significant effect on zeolite's effectiveness in the different industrial processes. This research aimed to study the textual properties of the NaX and FeX zeolites using the nitrogen adsorption-desorption technique at a constant low temperature. According to the International Union of Pure and Applied Chemistry, the adsorption-desorption isotherm showed that the studied materials were mixed kinds I/II isotherms and H3 type hysteresis. The Brunauer-Emmett-Teller isotherm was the best model to describe the nitrogen adsorption-desorption better than the Langmuir and Freundlich isotherms. The obtained adsorption capacity and Brunauer-Emmett-Teller surface area values for NaX were greater than FeX. According to the Kelvin equation, Barrett, Joyner, and Halenda model was used to determine pore size distribution, diameter, and average pore volume for the selected zeolites. The pore size distribution for NaX was wider than FeX zeolites, the pore diameter for NaX was less than FeX, and the average pore volume for FeX was greater than the value of NaX average pore volume. The comparative study was carried out with the previous studies, and the comparison showed that the textual properties of the modified zeolites agreed with other studies.